A kind of wrinkled polyacrylamide microsphere and its preparation method and application
The preparation of wrinkled polyacrylamide microspheres by thiolated PAMAM loaded with quantum dots solves the problems of instability and poor expansion of the existing microsphere system, and effectively blocking water, deep dissection and displacement in the oil field, improving crude oil recovery rate.
Patent Information
- Application Number
- CN202411766725.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-12-04
AI Technical Summary
The existing microsphere system is unstable and has poor expansion, making it difficult to meet the needs of improving crude oil recovery such as water blocking, deep dissection adjustment and displacement in oil field oil production.
Using thiolated PAMAM with metal copper and copper oxide quantum dots as matrix, wrinkled polyacrylamide microspheres were prepared by reverse phase emulsion polymerization to form nanoscale microspheres and form wrinkled structures on the surface.
It improves the stability and expansion of microspheres, enhances its resistance and blocking and oil discharging ability in high-temperature and high-salt environments, and effectively improves the recovery rate.
Smart Images

Figure CN119219838B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of petrochemical industry, and particularly relates to wrinkled polyacrylamide microspheres and a preparation method and application thereof. Background Art
[0002] Uneven water injection profiles will aggravate the heterogeneity of the reservoir, causing the injected water to advance and flow to varying degrees. Reservoir heterogeneity, scouring of injected water, migration of interlayer materials, expansion and dissolution, and other phenomena seriously affect the effect of water injection development in oil fields, resulting in a continuous decrease in recovery. Low permeability reservoirs often fail to inject water due to the complex fracture pore structure and small pore throats. High permeability reservoirs have strong water absorption capacity, so water injection often leads to the appearance of water flow channels in the formation. At present, most oil fields are in the medium and high water content period. In order to improve the recovery rate, that is, to improve the sweep efficiency of injected water and balance the water absorption profile, the main method is to find ways to expand the swept volume of injected water to improve the effect of water injection development. In order to improve the problems existing in the water injection process of low permeability reservoirs, it is necessary to optimize the performance of profile control agents so that they can meet the requirements of deep profile control.
[0003] Practice has proved that focusing on profile control, conducting relevant research on the recovery enhancement technology combining profile control and oil displacement, reducing the oil-water interfacial tension, and increasing the swept volume of injected water have great practical significance for improving the post-waterflooding development benefits of oil fields and improving the final recovery rate. At present, the commonly used profile control technology has achieved remarkable results in the actual application of oil fields, but traditional profile control agents also have some shortcomings. For example, granular profile control agents, although they have high strength and can well block the high permeability layer, are mainly used to improve the seepage situation near the injection well and increase the swept volume near the injection well. Their deep profile control effect is not great. Granular profile control agents often have large particle sizes and are mainly used to block the oil layer near the injection well. However, the residual oil saturation near the injection well is small, and the recovery rate is very low. The injected water will eventually bypass and enter the high permeability layer again. Although the underground cross-linked organic profile control system has the characteristics of mobility and can reach the deep part of the reservoir for profile control, its plugging strength cannot meet the requirements of high permeability formations. After a short period of plugging, it will be broken through by the injected water and has a short effective period. Therefore, based on the actual needs of the later stage of high water-content reservoir development, the development of deep-seated displacement agents that are effective in the long term and have a certain strength has become the core issue currently faced.
[0004] Deep profile control technology refers to the use of various organic and inorganic profile control and water plugging agents such as gel foam and polymer microspheres. These profile control and water plugging agents can penetrate deep into the reservoir, block high permeability reservoirs, force liquids to flow to low permeability reservoirs, and increase the volume of injected water in medium and low permeability reservoirs, thereby improving the recovery rate.
[0005] At present, polymer microspheres mainly have good water absorption and expansion performance, but large particle size, poor temperature and salt resistance, and will be damaged during migration to deep reservoirs, resulting in shallow penetration of polymer microspheres into the formation or poor plugging performance in deep reservoirs. Therefore, the development of microspheres with high temperature and salt resistance and strong formation penetration ability is the key to improving deep reservoir plugging.
[0006] Quantum dots are a new type of semiconductor nanomaterial, a type of semiconductor nanoparticle composed of II-VI or III-V elements with a radius smaller than or close to the exciton Bohr radius. Due to the influence of quantum size effect and dielectric confinement effect, quantum dots have unique properties, which makes quantum dots have great application potential in the fields of oil extraction and catalysis. The prior art generally directly uses quantum dots as tracers or oil displacement agents, and the application range is relatively narrow. CN115306362A directly uses quantum dots as oil displacement agents, and uses the extremely strong penetration and oil washing effects of quantum dots to penetrate into the rock surface to remove the oil film and improve the oil washing efficiency; however, its cost is relatively high, and it does not have the effect of blocking and regulating displacement. CN115181217A prepares core-shell microspheres with fluorescent tracing function, by introducing fluorescent quantum dots in the process of preparing the core microsphere solution, and then mixing and adsorbing with the shell monomer water to prepare the core-shell microsphere solution. The fluorescent quantum dots are located inside the core-shell fluorescent microspheres and will not detach, thereby improving the subsequent detection accuracy. The quantum dot microspheres are prepared into microspheres of ordinary morphology by direct in-situ polymerization process, and only the tracer function of quantum dots is used for detection, and the plugging and flooding effect is limited. The fluorescent microspheres prepared by CN117736722A, CN115247060A, etc. have smooth surfaces and cannot be used as flooding agents. Summary of the invention
[0007] One of the technical problems to be solved by the present invention is the problem of instability and poor expansion of the microsphere system in the prior art. A wrinkled polyacrylamide microsphere is provided. The microsphere has good stability and can be controllably expanded in brine, and can meet the on-site operation requirements for improving crude oil recovery such as water plugging, deep profile adjustment and displacement in oil field production.
[0008] The technical solution for achieving the purpose of the present invention is as follows:
[0009] A method for preparing wrinkled polyacrylamide microspheres comprises the following steps:
[0010] (1) adding thiolated PAMAM to a mixed solution containing metallic copper quantum dots and copper oxide quantum dots, performing ultrasonic dispersion, and drying to obtain thiolated PAMAM loaded with quantum dots; the mass ratio of the total weight of the metallic copper quantum dots and the copper oxide quantum dots to the thiolated PAMAM is (0.001-0.06):1;
[0011] (2) Under stirring conditions, acrylamide, acrylic acid, 2-acrylamide-2-methylpropanesulfonic acid and a cross-linking agent are added to water respectively, an alkali solution is added to adjust the pH, and nitrogen is passed to deoxygenate to obtain an aqueous phase;
[0012] (3) Adding the thiol-modified PAMAM loaded with quantum dots, a surfactant, and an azo initiator into an organic solvent, stirring evenly, and passing nitrogen gas to deoxygenate to obtain an oil phase;
[0013] (4) Under stirring conditions, the aqueous phase is added dropwise to the oil phase. After the addition is completed, the reaction is carried out at a temperature of 55-75°C for 1-4 hours to obtain wrinkled polyacrylamide microspheres.
[0014] In the previous work (CN118580443A), the inventor used silica of different particle sizes as reinforcing fillers and prepared polyacrylamide microspheres by dispersion polymerization, which improved the heat resistance and salt resistance of the microspheres to a certain extent. However, the microspheres have a smooth surface, large particle size, weak heat resistance and salt resistance, poor water absorption and expansion ability, and limited plugging and flooding effects. Subsequently, the inventors prepared lychee-shaped or rambutan-shaped polyacrylamide microspheres by loading copper oxide or metallic copper quantum dots. Although the above-mentioned polymer microspheres have certain heat resistance and salt resistance, they have large particle sizes or short "tentacles", and the improvement of oil displacement capacity is limited. In order to further improve the plugging and flooding capacity of polymer microspheres, the present invention introduces a dendritic PAMAM (polyamide-amine) polymer with a thiol end group as a matrix, and prepares thiol-loaded PAMAM quantum dots and copper oxide quantum dots.
[0015] PAMAM is a typical dendrimer. Compared with other traditional dendrimers, PAMAM has a large number of surface functional groups, intramolecular cavities and nanometer-scale dimensions, which provide a basis for loading quantum dots. Since the hydrocarbon chains in PAMAM dendrimers are lipophilic groups, but the carboxyl and amino groups they contain are hydrophilic groups, they not only have solubilizing and stabilizing effects, but can also combine with quantum dots through electrostatic adsorption; on the other hand, the presence of a large number of cavities on the surface and inside of PAMAM also helps with loading quantum dots.
[0016] However, directly using PAMAM cavities and electrostatic adsorption as the binding force for metal copper quantum dots will lead to uneven loading of quantum dots, unable to form a spatially ordered structure, and the binding force is weak, which will cause the quantum dots to fall off during the stirring process, affecting the stability of the product structure. In order to improve the stability and uniformity of PAMAM-loaded quantum dots, the present invention selects a dendritic PAMAM (polyamide-amine) polymer with a thiol end group as a matrix to load quantum dots. Compared with functional groups such as carboxyl and amino groups, thiol groups have a very strong coordination effect with metal quantum dots. PAMAM ligands containing thiol groups can firmly bind to quantum dots and can be used as stabilizers to prepare stable quantum dot dispersions. Since PAMAM has a high degree of geometric symmetry, the active groups on its surface are evenly distributed, and the surface becomes more and more crowded with the growth of generations. By introducing dense thiol functional groups on the PAMAM surface, strong coordination bonds can be formed with quantum dots, and the quantum dots can be evenly fixed on the outer surface of PAMAM.
[0017] Compared with metallic copper and other metal and its oxide quantum dots, CdTe, ZnS and other quantum dots, copper oxide quantum dots have spatial confinement between electron and hole pairs, which can generate additional energy. Moreover, copper oxide quantum dots are monoclinic p-type semiconductors with a narrow energy band gap (1.2 eV -1.8 eV), which can effectively adsorb azo initiators, reduce the activation energy required for azo initiators to produce free radicals, and accelerate the decomposition of initiators on the surface of quantum dots.
[0018] Metallic copper quantum dots are more active than copper oxide quantum dots, and because of their large surface area to volume ratio, the copper atoms exposed on the surface can provide a large number of active sites, thereby enhancing catalytic activity. The unpaired electrons of metallic copper quantum dots can be conjugated with the double bonds of acrylamide monomers, and free radicals can be generated to initiate polymerization reactions without the need for chemical initiators. Under heating conditions, the initiation rate is accelerated while also accelerating the monomer conversion rate. Compared with the previous technology of simply loading copper oxide quantum dots on large-particle mesoporous microspheres and using azo substances as initiators to prepare microspheres, the present invention uses thiol-PAMAM as a matrix to load metallic copper quantum dots and copper oxide quantum dots to initiate polymerization. The prepared microspheres have a smaller particle size and truly prepare nanoscale polymer microspheres. Due to the different polymerization rates directly initiated by metallic copper quantum dots and indirectly initiated by copper oxide quantum dots, the growth rates of the polymer with thiolated PAMAM loaded with quantum dots as the core are different in all directions; further, since metallic copper quantum dots and copper oxide quantum dots are evenly distributed on thiolated PAMAM, the polymerization rates of the monomers on the entire core surface are different in the three-dimensional direction. As the polymerization process proceeds, a wrinkled structure is gradually formed on the surface of the microspheres.
[0019] The two-dimensional lamellar wrinkled structure can not only play the role of cross-linking and interlocking to improve the plugging efficiency, but also its lamellar structure can play the role of "shovel" during the displacement of microspheres, thus improving the recovery rate. Compared with the one-dimensional linear structure, the lamellar structure is more conducive to the formation of a wedge-shaped area between the rock surface and the oil droplets. The wrinkled polyacrylamide microspheres of uniform size also follow the principle of overall entropy reduction and spontaneously arrange in order near the solid / oil / water three-phase contact line, forming a structural separation pressure in the restricted area, which prompts the contact line to move forward continuously. With the flow of nanofluids, a large number of particles accumulate at the front end, which can generate a large pressure at the vertex, separating the oil droplets from the rocks. At this time, under the action of the reservoir rock surface, the wrinkled polyacrylamide microspheres can be further adsorbed and form an interfacial film, which prevents the oil droplets from re-adhering to the rock surface with the help of the barrier effect of the film. The formation of structural separation pressure reduces the force between the oil droplets and the rocks and the flow resistance of crude oil in the reservoir, thereby improving the recovery rate.
[0020] Furthermore, the specific preparation process of thiolated PAMAM in step (1) is as follows: add thioglycolic acid or methyl thioglycolate to the aqueous solution of amino PAMAM, stir for reaction, and dry under reduced pressure to obtain thiolated PAMAM. The PAMAM with ethylenediamine as the core of the present invention is synthesized by diffusion method. First, the central core ethylenediamine and methyl acrylate are subjected to complete Michael addition reaction to obtain half-generation PAMAM with ester end group; the second step is the amidation reaction of ester end group half-generation PAMAM with excess ethylenediamine to obtain first-generation PAMAM with amino end group. Repeating the above two steps can obtain PAMAM of different integer generations that are continuously increasing. The outer layer of integer generation PAMAM dendrimer has a large number of amino groups, and the hydrocarbon chain inside is a lipophilic group, so PAMAM has the dual role of carrier and surfactant. The amino active groups on the surface of PAMAM are combined with quantum dots using thiol compounds as a connecting bridge. On the one hand, this reduces the surface energy of the quantum dots and improves their dispersibility; on the other hand, it prevents the oxidation or aggregation of metallic copper quantum dots or copper oxide quantum dots, thereby improving the stability of the quantum dots in the solvent.
[0021] Furthermore, the aminated PAMAM is a PAMAM of 4-10 integer generations; the molar ratio of the amino group on the aminated PAMAM to thioglycolic acid or methyl thioglycolate is 1:(1.1-1.5); the stirring reaction temperature is 45-55°C, and the reaction time is 7-10h.
[0022] Furthermore, in step (1), the mass ratio of the metal copper quantum dots to the copper oxide quantum dots is (0.5-2): 1. Furthermore, the mass ratio of the metal copper quantum dots to the copper oxide quantum dots is (1-1.5): 1; by adjusting the mass ratio of the metal copper quantum dots to the copper oxide quantum dots, the distribution of quantum dots on the surface of the microspheres can be adjusted, and the polymerization rate at different places on the surface of the microspheres can be indirectly adjusted, thereby promoting the formation of wrinkled morphology.
[0023] Furthermore, in step (2), the alkali solution is a sodium hydroxide solution or a potassium hydroxide solution, and the pH value is 6-7.
[0024] Furthermore, in step (2), the cross-linking agent is N,N-methylenebisacrylamide.
[0025] Furthermore, in step (3), the surfactant is one or both of Span-80 and Tween-80; the azo initiator is at least one of azobisisobutyronitrile and azobisisoheptylnitrile; and the organic solvent is white oil. Since the PAMAM dendrimer has a large number of hydrophilic groups such as ester groups and amide groups, it exhibits strong hydrophilicity. In order to improve the dispersion performance of PAMAM in organic solvents, the present invention deliberately disperses the thiolated PAMAM loaded with quantum dots and the surfactant used in the acrylamide polymerization process in the organic solvent in advance to prepare a premixed solution; it can not only prevent polar molecules such as acrylamide and acrylic acid monomers, N, N-methylenebisacrylamide crosslinking agents from combining with quantum dots in advance to prevent affecting the stability of quantum dots in the solution and the dispersion of thiolated PAMAM; it can also promote the adsorption of copper oxide quantum dots on azo initiators and promote the formation of wrinkled morphology.
[0026] Furthermore, the mass ratio of acrylamide, acrylic acid, 2-acrylamide-2-methylpropanesulfonic acid, crosslinker, surfactant, azo initiator and thiol-PAMAM loaded with quantum dots is (12-16): (4-8): (0.5-2.5): (1-3): (4-8): (0.05-0.2): 1; the mass ratio of water, organic solvent and thiol-PAMAM loaded with quantum dots is (70-80): (85-100): 1.
[0027] On the other hand, the present invention also provides an application of wrinkled polyacrylamide microspheres as a profile control and oil displacement agent. Acrylamide-based polymers are synthetic polymers used to enhance oil displacement. They have excellent rheological properties and are one of the most commonly used polymers in oil displacement applications. Due to the presence of a strong hydrophilic group, the polyacrylamide microspheres have good water absorption and swelling properties. They can absorb water and swell deep in the reservoir, plug the gaps, increase the volume of injected fluids, and thus improve the recovery rate. In order to enhance the stability of polymer microspheres in the harsh environment of high temperature and high salt in the reservoir, the main monomer acrylamide (AM) and the functional monomer acrylic acid (AA) are copolymerized, and an appropriate amount of cross-linking agent is added to prepare acrylamide-based quantum dot copolymer microspheres with a cross-linked structure. Compared with the previous microspheres with one-dimensional linear protrusions on the surface, the wrinkled structure can not only play a role in cross-linking and interlocking to improve the plugging efficiency, but also the wrinkled structure can play a technical effect of scraping oil and improve the recovery rate.
[0028] Beneficial effects: The present invention adopts the inverse emulsion polymerization method to prepare the wrinkled polymer microspheres, and the water-soluble monomer solution is evenly dispersed in the oil continuous phase through the emulsification effect of the surfactant, and the polymerization is initiated in the oil-in-water reaction system through the thiol-PAMAM loaded with quantum dots. The polymerization process is milder than the dispersion polymerization method, the conditions are easy to control, and the particle size of the prepared microspheres is more regular.
[0029] The microspheres prepared by polymerization initiated by using thiol-PAMAM as a matrix loaded with two quantum dots of metal copper and copper oxide have a smaller particle size, and nano-scale polymer microspheres are truly prepared. Since PAMAM has a high degree of geometric symmetry, by introducing dense thiol functional groups on the surface of PAMAM, a strong coordination bond can be formed with the quantum dots, and the quantum dots can be evenly fixed on the outer surface of PAMAM. The unpaired electrons of the metal copper quantum dots can be conjugated with the double bonds of the acrylamide monomer, and a free radical-initiated polymerization reaction can be generated without a chemical initiator. The copper oxide quantum dots have a monoclinic structure p-type semiconductor with a narrow energy band gap (1.2 eV-1.8 eV), which can effectively adsorb azo initiators, reduce the activation energy required for the azo initiators to generate free radicals, and accelerate the decomposition of the initiator on the surface of the quantum dots. Due to the different direct polymerization rates initiated by the metal copper quantum dots and the indirect polymerization rates initiated by the copper oxide quantum dots, the growth rates of the polymer with the thiol-PAMAM loaded with quantum dots as the core are different in all directions. As the polymerization process proceeds, a wrinkled structure is gradually formed on the surface of the microspheres. Compared with the previous microspheres with one-dimensional linear protrusions on the surface, the wrinkled structure can not only play the role of cross-linking and interlocking to improve the plugging efficiency, but also play the role of oil scraping. The microspheres have good stability and can be controllably expanded in salt water, which can meet the requirements of field operations such as water plugging, deep profile adjustment and displacement in oil field production to improve crude oil recovery. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is a scanning electron micrograph of the wrinkled polyacrylamide microspheres prepared in Example 8;
[0031] Figure 2 This is a scanning electron microscope image of polyacrylamide microspheres prepared in Comparative Example 1;
[0032] Figure 3 This is a scanning electron microscope image of the polyacrylamide microspheres prepared in Comparative Example 2. DETAILED DESCRIPTION
[0033] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art to which the present invention belongs. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items. The present invention will be further described below in conjunction with specific embodiments so that those skilled in the art can better understand the present invention and can implement it, but the embodiments are not intended to limit the present invention.
[0034] Example 1
[0035] A method for preparing wrinkled polyacrylamide microspheres comprises the following steps:
[0036] (1) Adding thiolated PAMAM to a chloroform solution containing metal copper quantum dots with an average particle size of 3 nm and copper oxide quantum dots with an average particle size of 5 nm, ultrasonically dispersing, and drying to obtain thiolated PAMAM loaded with quantum dots; the mass ratio of the total weight of the metal copper quantum dots and the copper oxide quantum dots to the thiolated PAMAM is 0.004:1; the specific preparation process of the thiolated PAMAM is: adding methyl thioglycolate to the aqueous solution of the aminated PAMAM, stirring the reaction, and drying under reduced pressure to obtain the thiolated PAMAM; the aminated PAMAM is an 8th generation PAMAM; the molar ratio of the amino group on the aminated PAMAM to the methyl thioglycolate is 1:1.3; the stirring reaction temperature is 50°C, and the reaction time is 8 hours; the mass ratio of the metal copper quantum dots to the copper oxide quantum dots is 1:1;
[0037] (2) Under stirring conditions, acrylamide, acrylic acid, 2-acrylamide-2-methylpropanesulfonic acid, and a cross-linking agent N,N-methylenebisacrylamide are added to water, the pH is adjusted to 6 by adding sodium hydroxide solution, and nitrogen is passed to deoxygenate to obtain an aqueous phase;
[0038] (3) Add the thiolated PAMAM loaded with quantum dots, surfactant, and azo initiator azobisisobutyronitrile to the organic solvent white oil, stir evenly, and pass nitrogen to deoxygenate to obtain an oil phase; the surfactant is a mixture of Span-80 and Tween-80 in a mass ratio of 4:1; the mass ratio of acrylamide, acrylic acid, 2-acrylamide-2-methylpropanesulfonic acid, crosslinker, surfactant, azo initiator, and thiolated PAMAM loaded with quantum dots is 12:4:0.5:1:4:0.05:1; the mass ratio of water, organic solvent, and thiolated PAMAM loaded with quantum dots is 70:85:1;
[0039] (4) Under stirring conditions, the aqueous phase is added dropwise to the oil phase. After the addition is completed, the mixture is reacted at 75°C for 1 hour to obtain wrinkled polyacrylamide microspheres.
[0040] Example 2
[0041] A method for preparing wrinkled polyacrylamide microspheres comprises the following steps:
[0042] (1) Adding thiolated PAMAM to a chloroform solution containing metal copper quantum dots with an average particle size of 3 nm and copper oxide quantum dots with an average particle size of 5 nm, ultrasonically dispersing, and drying to obtain thiolated PAMAM loaded with quantum dots; the mass ratio of the total weight of the metal copper quantum dots and the copper oxide quantum dots to the thiolated PAMAM is 0.06:1; the specific preparation process of thiolated PAMAM is: adding methyl thioglycolate to the aqueous solution of aminated PAMAM, stirring the reaction, and drying under reduced pressure to obtain the thiolated PAMAM; the aminated PAMAM is an 8th generation PAMAM; the molar ratio of the amino group on the aminated PAMAM to methyl thioglycolate is 1:1.3; the stirring reaction temperature is 50°C, and the reaction time is 8 hours; the mass ratio of the metal copper quantum dots to the copper oxide quantum dots is 1.5:1;
[0043] (2) Under stirring conditions, acrylamide, acrylic acid, 2-acrylamide-2-methylpropanesulfonic acid, and a cross-linking agent N,N-methylenebisacrylamide are added to water, the pH is adjusted to 7 by adding sodium hydroxide solution, and nitrogen is passed to deoxygenate to obtain an aqueous phase;
[0044] (3) Add the thiolated PAMAM loaded with quantum dots, surfactant, and azo initiator azobisisobutyronitrile to the organic solvent white oil, stir evenly, and pass nitrogen to deoxygenate to obtain an oil phase; the surfactant is a mixture of Span-80 and Tween-80 in a mass ratio of 4:1; the mass ratio of acrylamide, acrylic acid, 2-acrylamide-2-methylpropanesulfonic acid, crosslinker, surfactant, azo initiator, and thiolated PAMAM loaded with quantum dots is 16:8:2.5:3:8:0.2:1; the mass ratio of water, organic solvent, and thiolated PAMAM loaded with quantum dots is 80:100:1;
[0045] (4) Under stirring conditions, the aqueous phase is added dropwise to the oil phase. After the addition is completed, the mixture is reacted at 55°C for 4 hours to obtain wrinkled polyacrylamide microspheres.
[0046] Example 3
[0047] A method for preparing wrinkled polyacrylamide microspheres comprises the following steps:
[0048] (1) Adding thiolated PAMAM to a chloroform solution containing metal copper quantum dots with an average particle size of 3 nm and copper oxide quantum dots with an average particle size of 5 nm, ultrasonically dispersing, and drying to obtain thiolated PAMAM loaded with quantum dots; the mass ratio of the total weight of the metal copper quantum dots and the copper oxide quantum dots to the thiolated PAMAM is 0.005:1; the specific preparation process of thiolated PAMAM is: adding methyl thioglycolate to the aqueous solution of aminated PAMAM, stirring the reaction, and drying under reduced pressure to obtain the thiolated PAMAM; the aminated PAMAM is an 8th generation PAMAM; the molar ratio of the amino group on the aminated PAMAM to the methyl thioglycolate is 1:1.3; the stirring reaction temperature is 50°C, and the reaction time is 8 hours; the mass ratio of the metal copper quantum dots to the copper oxide quantum dots is 1.1:1;
[0049] (2) Under stirring conditions, acrylamide, acrylic acid, 2-acrylamide-2-methylpropanesulfonic acid, and a cross-linking agent N,N-methylenebisacrylamide are added to water, the pH is adjusted to 7 by adding sodium hydroxide solution, and nitrogen is passed to deoxygenate to obtain an aqueous phase;
[0050] (3) Add the thiolated PAMAM loaded with quantum dots, surfactant, and azo initiator azobisisobutyronitrile to the organic solvent white oil, stir evenly, and pass nitrogen to deoxygenate to obtain an oil phase; the surfactant is a mixture of Span-80 and Tween-80 in a mass ratio of 3:1; the mass ratio of acrylamide, acrylic acid, 2-acrylamide-2-methylpropanesulfonic acid, crosslinker, surfactant, azo initiator, and thiolated PAMAM loaded with quantum dots is 12:8:0.5:3:4:0.2:1; the mass ratio of water, organic solvent, and thiolated PAMAM loaded with quantum dots is 70:100:1;
[0051] (4) Under stirring conditions, the aqueous phase is added dropwise to the oil phase. After the addition is completed, the mixture is reacted at 60°C for 2.5 hours to obtain wrinkled polyacrylamide microspheres.
[0052] Example 4
[0053] A method for preparing wrinkled polyacrylamide microspheres comprises the following steps:
[0054] (1) Adding thiolated PAMAM to a chloroform solution containing metal copper quantum dots with an average particle size of 3 nm and copper oxide quantum dots with an average particle size of 5 nm, ultrasonically dispersing, and drying to obtain thiolated PAMAM loaded with quantum dots; the mass ratio of the total weight of the metal copper quantum dots and the copper oxide quantum dots to the thiolated PAMAM is 0.01:1; the specific preparation process of thiolated PAMAM is: adding methyl thioglycolate to the aqueous solution of aminated PAMAM, stirring the reaction, and drying under reduced pressure to obtain the thiolated PAMAM; the aminated PAMAM is an 8th generation PAMAM; the molar ratio of the amino group on the aminated PAMAM to the methyl thioglycolate is 1:1.3; the stirring reaction temperature is 50°C, and the reaction time is 8 hours; the mass ratio of the metal copper quantum dots to the copper oxide quantum dots is 1.2:1;
[0055] (2) Under stirring conditions, acrylamide, acrylic acid, 2-acrylamide-2-methylpropanesulfonic acid, and a cross-linking agent N,N-methylenebisacrylamide are added to water, the pH is adjusted to 6 by adding sodium hydroxide solution, and nitrogen is passed to deoxygenate to obtain an aqueous phase;
[0056] (3) Add the thiolated PAMAM loaded with quantum dots, surfactant, and azo initiator azobisisobutyronitrile into the organic solvent white oil, stir evenly, and pass nitrogen to deoxygenate to obtain the oil phase; the surfactant is a mixture of Span-80 and Tween-80 in a mass ratio of 4:1; the mass ratio of acrylamide, acrylic acid, 2-acrylamide-2-methylpropanesulfonic acid, crosslinker, surfactant, azo initiator, and thiolated PAMAM loaded with quantum dots is 13:5:1:1.5:5:0.1:1; the mass ratio of water, organic solvent, and thiolated PAMAM loaded with quantum dots is 75:95:1;
[0057] (4) Under stirring conditions, the aqueous phase is added dropwise to the oil phase. After the addition is completed, the mixture is reacted at 60°C for 3 hours to obtain wrinkled polyacrylamide microspheres.
[0058] Example 5
[0059] A method for preparing wrinkled polyacrylamide microspheres comprises the following steps:
[0060] (1) Adding thiolated PAMAM to a chloroform solution containing metal copper quantum dots with an average particle size of 3 nm and copper oxide quantum dots with an average particle size of 5 nm, ultrasonically dispersing, and drying to obtain thiolated PAMAM loaded with quantum dots; the mass ratio of the total weight of the metal copper quantum dots and the copper oxide quantum dots to the thiolated PAMAM is 0.04:1; the specific preparation process of thiolated PAMAM is: adding methyl thioglycolate to the aqueous solution of aminated PAMAM, stirring the reaction, and drying under reduced pressure to obtain the thiolated PAMAM; the aminated PAMAM is an 8th generation PAMAM; the molar ratio of the amino group on the aminated PAMAM to the methyl thioglycolate is 1:1.3; the stirring reaction temperature is 50°C, and the reaction time is 8 hours; the mass ratio of the metal copper quantum dots to the copper oxide quantum dots is 1.4:1;
[0061] (2) Under stirring conditions, acrylamide, acrylic acid, 2-acrylamide-2-methylpropanesulfonic acid, and a cross-linking agent N,N-methylenebisacrylamide are added to water, the pH is adjusted to 7 by adding sodium hydroxide solution, and nitrogen is passed to deoxygenate to obtain an aqueous phase;
[0062] (3) Add the thiolated PAMAM loaded with quantum dots, surfactant, and azo initiator azobisisobutyronitrile to the organic solvent white oil, stir evenly, and pass nitrogen to deoxygenate to obtain an oil phase; the surfactant is a mixture of Span-80 and Tween-80 in a mass ratio of 4:1; the mass ratio of acrylamide, acrylic acid, 2-acrylamide-2-methylpropanesulfonic acid, crosslinker, surfactant, azo initiator, and thiolated PAMAM loaded with quantum dots is 15:7:2:2.5:7:0.15:1; the mass ratio of water, organic solvent, and thiolated PAMAM loaded with quantum dots is 78:95:1;
[0063] (4) Under stirring conditions, the aqueous phase is added dropwise to the oil phase. After the addition is completed, the mixture is reacted at 70°C for 2 h to obtain wrinkled polyacrylamide microspheres.
[0064] Example 6
[0065] A method for preparing wrinkled polyacrylamide microspheres comprises the following steps:
[0066] (1) Adding thiolated PAMAM to a chloroform solution containing metal copper quantum dots with an average particle size of 3 nm and copper oxide quantum dots with an average particle size of 5 nm, ultrasonically dispersing, and drying to obtain thiolated PAMAM loaded with quantum dots; the mass ratio of the total weight of the metal copper quantum dots and the copper oxide quantum dots to the thiolated PAMAM is 0.03:1; the specific preparation process of thiolated PAMAM is: adding methyl thioglycolate to the aqueous solution of aminated PAMAM, stirring the reaction, and drying under reduced pressure to obtain the thiolated PAMAM; the aminated PAMAM is an 8th generation PAMAM; the molar ratio of the amino group on the aminated PAMAM to the methyl thioglycolate is 1:1.3; the stirring reaction temperature is 50°C, and the reaction time is 8 hours; the mass ratio of the metal copper quantum dots to the copper oxide quantum dots is 0.5:1;
[0067] (2) Under stirring conditions, acrylamide, acrylic acid, 2-acrylamide-2-methylpropanesulfonic acid, and a cross-linking agent N,N-methylenebisacrylamide are added to water, the pH is adjusted to 7 by adding sodium hydroxide solution, and nitrogen is passed to deoxygenate to obtain an aqueous phase;
[0068] (3) Add the thiolated PAMAM loaded with quantum dots, surfactant, and azo initiator azobisisobutyronitrile to the organic solvent white oil, stir evenly, and pass nitrogen to deoxygenate to obtain an oil phase; the surfactant is a mixture of Span-80 and Tween-80 in a mass ratio of 4:1; the mass ratio of acrylamide, acrylic acid, 2-acrylamide-2-methylpropanesulfonic acid, crosslinker, surfactant, azo initiator, and thiolated PAMAM loaded with quantum dots is 14:6:2:2:6:0.1:1; the mass ratio of water, organic solvent, and thiolated PAMAM loaded with quantum dots is 80:100:1;
[0069] (4) Under stirring conditions, the aqueous phase is added dropwise to the oil phase. After the addition is completed, the mixture is reacted at 60°C for 3 hours to obtain wrinkled polyacrylamide microspheres.
[0070] Example 7
[0071] A method for preparing wrinkled polyacrylamide microspheres comprises the following steps:
[0072] (1) Adding thiolated PAMAM to a chloroform solution containing metal copper quantum dots with an average particle size of 3 nm and copper oxide quantum dots with an average particle size of 5 nm, ultrasonically dispersing, and drying to obtain thiolated PAMAM loaded with quantum dots; the mass ratio of the total weight of the metal copper quantum dots and the copper oxide quantum dots to the thiolated PAMAM is 0.03:1; the specific preparation process of thiolated PAMAM is: adding methyl thioglycolate to the aqueous solution of aminated PAMAM, stirring the reaction, and drying under reduced pressure to obtain the thiolated PAMAM; the aminated PAMAM is an 8th generation PAMAM; the molar ratio of the amino group on the aminated PAMAM to the methyl thioglycolate is 1:1.3; the stirring reaction temperature is 50°C, and the reaction time is 8 hours; the mass ratio of the metal copper quantum dots to the copper oxide quantum dots is 2:1;
[0073] (2) Under stirring conditions, acrylamide, acrylic acid, 2-acrylamide-2-methylpropanesulfonic acid, and a cross-linking agent N,N-methylenebisacrylamide are added to water, the pH is adjusted to 7 by adding sodium hydroxide solution, and nitrogen is passed to deoxygenate to obtain an aqueous phase;
[0074] (3) Add the thiolated PAMAM loaded with quantum dots, surfactant, and azo initiator azobisisobutyronitrile to the organic solvent white oil, stir evenly, and pass nitrogen to deoxygenate to obtain an oil phase; the surfactant is a mixture of Span-80 and Tween-80 in a mass ratio of 4:1; the mass ratio of acrylamide, acrylic acid, 2-acrylamide-2-methylpropanesulfonic acid, crosslinker, surfactant, azo initiator, and thiolated PAMAM loaded with quantum dots is 14:6:2:2:6:0.1:1; the mass ratio of water, organic solvent, and thiolated PAMAM loaded with quantum dots is 80:100:1;
[0075] (4) Under stirring conditions, the aqueous phase is added dropwise to the oil phase. After the addition is completed, the mixture is reacted at 60°C for 3 hours to obtain wrinkled polyacrylamide microspheres.
[0076] Example 8
[0077] A method for preparing wrinkled polyacrylamide microspheres comprises the following steps:
[0078] (1) Adding thiolated PAMAM to a chloroform solution containing metal copper quantum dots with an average particle size of 3 nm and copper oxide quantum dots with an average particle size of 5 nm, ultrasonically dispersing, and drying to obtain thiolated PAMAM loaded with quantum dots; the mass ratio of the total weight of the metal copper quantum dots and the copper oxide quantum dots to the thiolated PAMAM is 0.03:1; the specific preparation process of thiolated PAMAM is: adding methyl thioglycolate to the aqueous solution of aminated PAMAM, stirring the reaction, and drying under reduced pressure to obtain the thiolated PAMAM; the aminated PAMAM is an 8th generation PAMAM; the molar ratio of the amino group on the aminated PAMAM to the methyl thioglycolate is 1:1.3; the stirring reaction temperature is 50°C, and the reaction time is 8 hours; the mass ratio of the metal copper quantum dots to the copper oxide quantum dots is 1.3:1;
[0079] (2) Under stirring conditions, acrylamide, acrylic acid, 2-acrylamide-2-methylpropanesulfonic acid, and a cross-linking agent N,N-methylenebisacrylamide are added to water, the pH is adjusted to 7 by adding sodium hydroxide solution, and nitrogen is passed to deoxygenate to obtain an aqueous phase;
[0080] (3) Add the thiolated PAMAM loaded with quantum dots, surfactant, and azo initiator azobisisobutyronitrile to the organic solvent white oil, stir evenly, and pass nitrogen to deoxygenate to obtain an oil phase; the surfactant is a mixture of Span-80 and Tween-80 in a mass ratio of 4:1; the mass ratio of acrylamide, acrylic acid, 2-acrylamide-2-methylpropanesulfonic acid, crosslinker, surfactant, azo initiator, and thiolated PAMAM loaded with quantum dots is 14:6:2:2:6:0.1:1; the mass ratio of water, organic solvent, and thiolated PAMAM loaded with quantum dots is 80:100:1;
[0081] (4) Under stirring conditions, the aqueous phase is added dropwise to the oil phase. After the addition is completed, the mixture is reacted at 60°C for 3 hours to obtain wrinkled polyacrylamide microspheres.
[0082] Comparative Example 1
[0083] The preparation process is basically the same as that of Example 8, except that copper oxide quantum dots are not added in step (1), and the mass ratio of metallic copper quantum dots to thiolated PAMAM is 0.03:1.
[0084] Comparative Example 2
[0085] The preparation process is basically the same as that of Example 8, except that no metallic copper quantum dots are added in step (1), and the mass ratio of copper oxide quantum dots to thiolated PAMAM is 0.03:1.
[0086] Performance Testing:
[0087] The polyacrylamide microspheres prepared in Examples 1-8 and Comparative Examples 1-2 were dispersed in simulated formation water with a mineralization of 30,000 mg / L, and expanded at 80° C. for different time periods. The expansion multiples were measured. The results are shown in Table 1.
[0088] Low permeability cores were selected for evaluation of oil displacement effect: first, the cores were saturated with simulated formation water to determine their pore volume; then, the cores were saturated with simulated crude oil; the cores were displaced with simulated formation water until the outlet end stopped producing oil, and the recovery factor A was determined; polyacrylamide microsphere dispersion was injected into the cores and placed at 65°C for 5 days; the cores were displaced with simulated formation water again until the outlet end stopped producing oil, and the recovery factor B was determined; the recovery factor increase was C (%) = (BA) / AX 100%, and the results are shown in Table 1.
[0089]
[0090] Depend on Figure 1 It can be seen that the present invention prepares wrinkled polyacrylamide microspheres, and the microspheres have a small particle size of about 100nm; the surface of the microspheres is evenly dispersed with wrinkled structures, which is conducive to the formation of an interface film during oil displacement. The formation of the above structure increases the specific surface area of the microspheres. During the water absorption and expansion process, the larger specific surface area can effectively disperse the internal stress and prevent stress concentration from occurring, which leads to the rupture of the microspheres; moreover, the wrinkled structure has a higher expansion rate after water absorption than the microsphere body, which is conducive to improving the plugging rate. More importantly, compared with the one-dimensional linear structure raised on the surface of the sphere, the lamellar structure is more conducive to the microspheres forming a wedge-shaped area between the rock surface and the oil droplets, so that the oil droplets are separated from the rock. At this time, under the action of the reservoir rock surface, the wrinkled polyacrylamide microspheres can be further adsorbed and form an interface film, and the barrier effect of the film is used to prevent the oil droplets from re-adhering to the rock surface. The formation of structural separation pressure reduces the force between the oil droplets and the rock and the flow resistance of crude oil in the reservoir, thereby improving the recovery rate.
[0091] Comparative Examples 1 and 2 show that adding a single quantum dot does not lead to differentiation of the polymerization rate of monomers on the surface of the sphere, and does not form a wrinkled structure. This is because, compared with the dispersion polymerization method of a single solvent type, the inverse emulsion polymerization will form an oil-in-water structure. The formation of a two-phase structure will weaken the influence of different positions of a single quantum dot on the polymerization rate, which is reflected in the microsphere morphology, that is, the formation of a relatively smooth surface, which is not conducive to the improvement of microsphere plugging and oil displacement efficiency.
[0092] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A method for preparing wrinkled polyacrylamide microspheres, characterized in that: The following steps are involved: (1) adding thiolated PAMAM to a mixed solution containing metallic copper quantum dots and copper oxide quantum dots, performing ultrasonic dispersion, and drying to obtain thiolated PAMAM loaded with quantum dots; the mass ratio of the total weight of the metallic copper quantum dots and the copper oxide quantum dots to the thiolated PAMAM is (0.001-0.06):1; (2) Under stirring conditions, acrylamide, acrylic acid, 2-acrylamide-2-methylpropanesulfonic acid and a cross-linking agent are added to water respectively, an alkali solution is added to adjust the pH, and nitrogen is passed to deoxygenate to obtain an aqueous phase; (3) Adding thiolated PAMAM loaded with quantum dots, surfactant and azo initiator into an organic solvent, stirring evenly, and passing nitrogen to deoxygenate to obtain an oil phase; the mass ratio of acrylamide, acrylic acid, 2-acrylamide-2-methylpropanesulfonic acid, crosslinking agent, surfactant, azo initiator and thiolated PAMAM loaded with quantum dots is (12-16): (4-8): (0.5-2.5): (1-3): (4-8): (0.05-0.2): 1; (4) Under stirring conditions, the aqueous phase is added dropwise to the oil phase. After the addition is completed, the reaction is carried out at a temperature of 55-75°C for 1-4 hours to obtain wrinkled polyacrylamide microspheres.
2. The method for preparing wrinkled polyacrylamide microspheres according to claim 1, characterized in that: The specific preparation process of the thiolated PAMAM in step (1) is as follows: adding thioglycolic acid or methyl thioglycolate to the aqueous solution of amino PAMAM, stirring for reaction, and drying under reduced pressure to obtain the thiolated PAMAM.
3. The method for preparing wrinkled polyacrylamide microspheres according to claim 2, characterized in that: The aminated PAMAM is a PAMAM of 4-10 integer generations; the molar ratio of the amino group on the aminated PAMAM to thioglycolic acid or methyl thioglycolate is 1:(1.1-1.5); the stirring reaction temperature is 45-55°C, and the reaction time is 7-10h.
4. The method for preparing wrinkled polyacrylamide microspheres according to claim 1, characterized in that: In step (1), the mass ratio of metallic copper quantum dots to copper oxide quantum dots is (0.5-2):
1.
5. The method for preparing wrinkled polyacrylamide microspheres according to claim 1, characterized in that: The alkali solution in step (2) is a sodium hydroxide solution or a potassium hydroxide solution, and the pH value is 6-7.
6. The method for preparing wrinkled polyacrylamide microspheres according to claim 1, characterized in that: In step (2), the cross-linking agent is N,N-methylenebisacrylamide.
7. The method for preparing wrinkled polyacrylamide microspheres according to claim 1, characterized in that: In step (3), the surfactant is one or both of Span-80 and Tween-80; the azo initiator is at least one of azobisisobutyronitrile and azobisisoheptanenitrile; and the organic solvent is white oil.
8. The method for preparing wrinkled polyacrylamide microspheres according to claim 1, characterized in that: The mass ratio of water, organic solvent and thiolated PAMAM loaded with quantum dots is (70-80):(85-100):
1.
9. A wrinkled polyacrylamide microsphere, characterized in that: The wrinkled polyacrylamide microspheres are prepared by the preparation method of any one of claims 1 to 8.
10. Use of the wrinkled polyacrylamide microspheres as claimed in claim 9 as a profile control and oil displacement agent.
Citation Information
Patent Citations
Preparation method of core-shell type fluorescent microsphere profile control and plugging agent applied to offshore oilfield high-permeability reservoir based on quantum dots
CN115181217A
Quantum dot light-emitting film, preparation and application of quantum dot light-emitting film in white-light Mini-LED device
CN115247060A
Application of quantum dots in unconventional oil reservoir exploitation, oil-displacing agent and method for increasing yield by using oil-displacing agent
CN115306362A
High-brightness and high-stability water-soluble quantum dot fluorescent microsphere and preparation method thereof
CN117736722A
Temperature-resistant and salt-resistant polymer microsphere and preparation method thereof
CN118580443A